1970
DOI: 10.3329/dujbs.v21i1.9742
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Abundance In Indian White Shrimp, Penaeus Indicus Collected From Two Different Market Conditions Of Dhaka City

Abstract: A study was accomplished in regard to the microbiological abundance in the muscle of Indian White Shrimp (Penaeus indicus) collected from three departmental chain shops and three local markets of Dhaka metropolitan city has been assessed in terms of total bacterial count (TBC), coliform and Salmonella? Shigella (SS) counts. The TBC ranged from 2.1 ± 0.20 × 104 to 4.7 ± 0.50 × 105 cfu/g for departmental shop frozen shrimp and 4.2 ± 0.45 × 106 to 1.3 ± 0.50 × 108 cfu/g for local market iced shrimp. The total col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…Staphylococci counts of live crabs were not within the acceptable limit (10 3 cfu g -1 ) recommended by ICMSF (1998). The results confirmed that the samples of local markets contained high pathogenic bacterial load which are supposed to be a threat to food safety creating food borne diseases (Nilla, et al, 2012).The high total aerobic counts is an indication of reduced shelf-life for the crab meats while the high coliform and staphylococcal counts is an indication of potential food infection/ intoxication (Buchanan, 1991). The TBC counts of this study were more or less similar to the study of Lalitha et al, 2012.…”
Section: Resultssupporting
confidence: 52%
“…Staphylococci counts of live crabs were not within the acceptable limit (10 3 cfu g -1 ) recommended by ICMSF (1998). The results confirmed that the samples of local markets contained high pathogenic bacterial load which are supposed to be a threat to food safety creating food borne diseases (Nilla, et al, 2012).The high total aerobic counts is an indication of reduced shelf-life for the crab meats while the high coliform and staphylococcal counts is an indication of potential food infection/ intoxication (Buchanan, 1991). The TBC counts of this study were more or less similar to the study of Lalitha et al, 2012.…”
Section: Resultssupporting
confidence: 52%
“…Besides, Vibrio spp. present mainly in intestine of fish and as the whole fish was considered for microbial analysis, so the density was high (Nilla et al 2012a). This result revealed that microbial quality of local markets was not good due to presence of Vibrio spp.…”
Section: Nutrient Compositionmentioning
confidence: 99%
“…It concerns with animal protein derived from marketed fish, fishery products, meats and meat products that creates a high risk commodity regarding to microbial contaminations, adulterants and natural toxicity (Nilla et al 2012a). Besides, bacteriological *Corresponding author: E-mail: mgmustafabd@yahoo.com 1 Department of Microbiology, University of Dhaka, Dhaka-1000, Bangladesh. quality is directly related to the spoilage of fish and becomes the cause of outbreak of food poisoning (Nilla et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…It concerns with animal protein derived from marketed fish, fishery products, meats and meat products that creates a high risk commodity regarding to pathogenic/ microbial contaminations, adulterants and natural toxicity causes death [1] . Bacteriological quality of fish concerns to the spoilage and in some cases creates chance for the outbreak of food poisoning [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, anthropogenic and biological contagions depreciate the water quality of the shrimp farming area which cause great difficulties in shrimp exporting with the international quality standard. Shrimps, exported principally to USA, Japan and Europe from Bangladesh [3] , is threatened for low quality of processed shrimp products due to small size, bacterial load or presence of chemical residue levels [1,2] . Raw or frozen shrimp deteriorated by improper handling are responsible for causing foodborne diseases [1] and diseases transmission.…”
Section: Introductionmentioning
confidence: 99%